2015
DOI: 10.1007/s13213-015-1112-3
|View full text |Cite
|
Sign up to set email alerts
|

Plant-growth-promoting rhizobacteria: drought stress alleviators to ameliorate crop production in drylands

Abstract: Drylands are known for being a drought stressed environment, which is an alarming constraint to crop productivity. To rescue plant growth in such stressful conditions, plant-growth-promoting rhizobacteria (PGPR) are a bulwark against drought stress and imperilled sustainability of agriculture in drylands. PGPR mitigates the impact of drought stress on plants through a process called rhizobacterial-induced drought endurance and resilience (RIDER), which includes physiological and biochemical changes. Various RI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
166
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(173 citation statements)
references
References 89 publications
4
166
0
3
Order By: Relevance
“…Inoculation of PGPR can also minimize the impact of water deficit stress on plant growth and development owing to their ability of ACC deaminase, EPS and osmolyte production . In the present study, it was observed that seed inoculation with P. fluorescens reduced water deficit‐induced growth suppression in cucumber, and significantly better shoot and root growth was observed than in un‐inoculated plants.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Inoculation of PGPR can also minimize the impact of water deficit stress on plant growth and development owing to their ability of ACC deaminase, EPS and osmolyte production . In the present study, it was observed that seed inoculation with P. fluorescens reduced water deficit‐induced growth suppression in cucumber, and significantly better shoot and root growth was observed than in un‐inoculated plants.…”
Section: Discussionsupporting
confidence: 56%
“…Various researchers have reported that inoculation with PGPR containing ACC deaminase activity can reduce the stress‐induced negative impact of ethylene on root growth by degrading its immediate precursor ACC . Moreover, the production of EPS by bacteria protects plants from desiccation . Therefore inoculation with P. fluorescens resulted in the development of a better root system, which subsequently affected shoot growth positively.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Most documented growth enhancement determined by these bacteria is associated with high level of IAA, which has been proven to alleviate salt stress [88] and EPS production that may help in maintaining a film of hydration around the roots and/or help re-establishing favourable water potential gradients under water limitations. These functions have been proven useful under saline stress [89], extremes of temperature, pH, salinity, and drought [87,90]. Inoculation of maize with Azotobacter strains has been shown to have general positive effects under saline stress by facilitating uptake of K + and exclusion of Na + as well as increasing phosphorous and nitrogen availability [24].…”
Section: Microorganisms Affecting Stress Tolerancementioning
confidence: 99%
“…Cellular dehydration induced biosynthesis of ABA, a stress hormone during water deficit condition (Kaushal and Wani, 2015). In addition to IAA, production of ABA by Azospirillum lipoferum alleviated drought stress in maize plants (Cohen et al, 2009).…”
Section: Effect Of Pgpr On Phytohormonal Levelmentioning
confidence: 99%